Chapter 9 From Conference to Community Interpreter Education The Transformation of Interpreter Education in Slovenia - K. Pokorn, Nike (Taylor & Francis, 2021)
The aim of the chapter is to determine whether the current education of interpreters in the Republic of Slovenia responds to the needs of the society. In order to do that, the chapter first briefly outlines the development of the education of Slovene interpreters from its beginnings to the present. By drawing on the results of a nation-wide survey of language-support needs in Slovene healthcare institutions from 2016, which gathered responses of 564 healthcare workers, and on statistics of the Ministry of Interior Affairs of the Republic of Slovenia providing the countries of origin of applicants for international protection in Slovenia in the period between 2013 and 2019, the language needs on the contemporary Slovene society are outlined. These needs are then compared to the results provided by a nation-wide survey of interpreters and sworn interpreters from 2020 (n=123) focusing on language combinations they offer and identifying different settings in which they work. The results of this comparison show that there is a serious mismatch between the needs of the society and the existing language profiles of professional interpreters in the market, which results in the fact that ad-hoc interpreters are used for almost all the languages of newly arrived migrants with negative consequences for society at large. The chapter concludes with the description of educational efforts aimed at remedying the situation: first, a short specialisation program for sworn interpreters introduced in 2018, and second, the education of teachers of community interpreters for Albanian, Arabic and Persian which took place from 2019 to 2020.